PENGEMBANGAN APLIKASI INFORMASI RUTE ANGKUTAN KOTA BANDAR LAMPUNG BERBASIS ANDROID - Rico Andrian; Febi Eka Febriansyah; Basir Efendi (Jurnal Komputasi, 2019)
This research is done to design and build Information Application of Bandar Lampung City’s Public Transportation with Android. This application can be used as a media to know about Bandar Lampung’s Public Transportation and the routes which is used by Bandar Lampung City’s public transportation, and the benefit of this application is to help citizen who does not know Bandar Lampung City to know about the routes of Bandar Lampung City’s public transportation. Application of Bandar Lampung City’s Public Transportation uses java programming language. Development of the application uses Unified Process (UP) method and is designed with Unified Modeling Language (UML). The result produced in the test using Equivalence Paritioning shows that system’s management of rules are able to run well and the system can provide information well. Base on testing data, this application is categorized as User Friendly with the average of 83,67% (Very Good).